2018
DOI: 10.1007/978-3-030-02330-0_3
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning and AI for Risk Management

Abstract: We explore how machine learning and artificial intelligence (AI) solutions are transforming risk management. A non-technical overview is first given of the main machine learning and AI techniques of benefit to risk management. Then a review is provided, using current practice and empirical evidence, of the application of these techniques to the risk management fields of credit risk, market risk, operational risk, and compliance ('RegTech'). We conclude with some thoughts on current limitations and views on how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(70 citation statements)
references
References 21 publications
0
43
0
Order By: Relevance
“…A survey of the top 1000 firms in the United States on AI implementation in their firms found that their biggest concern in the implementation of AI was the readiness and ability of staff to understand and work with these new solutions. Training a skilled cohort of staff is something that will take time [67]. World Economic Forum data show that by 2020, machines and algorithms will create 133 million job positions of new functions.…”
Section: Discussion On Recommendations For Crmf and Ai Applicabilitymentioning
confidence: 99%
See 4 more Smart Citations
“…A survey of the top 1000 firms in the United States on AI implementation in their firms found that their biggest concern in the implementation of AI was the readiness and ability of staff to understand and work with these new solutions. Training a skilled cohort of staff is something that will take time [67]. World Economic Forum data show that by 2020, machines and algorithms will create 133 million job positions of new functions.…”
Section: Discussion On Recommendations For Crmf and Ai Applicabilitymentioning
confidence: 99%
“…As Aziz and Dowling suggest, firms cannot simply 'apply' a machine learning risk management solution, but it is rather a continuous process requiring a constant evaluation of whether their particular machine learning solution is currently considered best practice. When it comes to AI, where there is some or full automation of processes, from data gathering to decision-making, the need for human oversight will become even more pressing [67].…”
Section: Discussion On Recommendations For Crmf and Ai Applicabilitymentioning
confidence: 99%
See 3 more Smart Citations